Sedentary behaviour is an independent predictor of diabetic foot ulcer development: An 8-year prospective study. (July 2021) - Orlando, Giorgio; Reeves, Neil D.; Boulton, Andrew J.M.; Ireland, Alex; Federici, Giovanni; Federici, Adalberto; Haxhi, Jonida; Pugliese, Giuseppe; Balducci, Stefano
Highlights: SED-time is a powerful predictor of risk of foot ulcer in people with DPN. DPN patients who are likely to develop a foot ulcer spend at least 12 h of sedentary time. The monitoring of SED-time should be included in the standard care of diabetic patients and strategies aimed at reducing it remain an unmet necessity. Abstract: Aims: To prospectively explore the association between sedentary time (SED-time) and the development of diabetic foot ulcer (DFU) in people with diabetic peripheral neuropathy (DPN). Methods: 175 DPN individuals who attended the annual evaluation for the SAMBA Study (2012–2019) were included. Main outcome measure was the first diagnosis of DFU. SED-time was measured by the PAS 2.1 questionnaire. Nerve function was evaluated by nerve conduction studies. Vascular function was assessed by Ankle-brachial index (ABI) and pedal pulses. Foot deformity and skin dryness were examined by visual inspection. Results: 62 participants (35.5%) developed a DFU during the study. SED-time was significantly higher in people who developed DFUs (12.8 ± 3.0 vs 9.4 ± 3.1 h/day). Logistic regression showed that among several nervous (motor amplitude, OR 0.33, 95% CI, 0.18–0.60; sensory amplitude, 0.85, 0.77–0.94) and vascular parameters (ABI, 0.23, 0.1–0.61; pedal pulses, 2.81, 0.12–0.63) and foot characteristics (deformity, 2.63, 1.30–5.32; skin dryness, 2.04, 0.95–4.37), SED-time was one of the strongest variables contributing to the development of DFUs (2.95, 1.45–6.44). Conclusions: SED-time is an independent predictor of the risk of DFU in people with DPN. The monitoring of SED-time with strategies aimed at reducing it should be included in the standard care of diabetic patients.